Multiple endocrine neoplasia type 2A (Sipple syndrome) - O.V. Safonova (Danylo Halytsky Lviv National Medical University, 2017)
Aim. To improve diagnosis and differential diagnosis of diseases with hypertension, including multiple endocrine meoplasia, their timely diagnosis and appropriate treatment of patients.